Arctic in the System of Global Priorities of the Beijing: a View from Russia - V. V. Karlusov (Vestnik MGIMO-Universiteta)
Globalization of Chinese economy in 1990–2010s is accompanied by the PRC’ greater political activity towards the Arctic. Based on the methodology of fundamental systemic analysis, the article provides a critical assessment of the real interests, forming general strategy, potential of resources and probable prospects of the Peking’s arctic policy. The final conclusions and recommendations are significant and relevant for China as well as for the arctic states including Russia.